2013
DOI: 10.1063/1.4772459
|View full text |Cite
|
Sign up to set email alerts
|

Directional-dependent coercivities and magnetization reversal mechanisms in fourfold ferromagnetic systems of varying sizes

Abstract: Different types of reversal processes, including either uniform-rotation or domain-wall driven processes, were indentified in magnetic nano-wires of four-fold symmetry using micromagnetic simulations. Iron wires were tested for diameters ranging from 6 nm up to 20 nm, while their lengths were taken from 30 nm to 70 nm range, and for several directions of externally applied magnetic field. Physical parameters of presented low-dimensional structures enabled reversal via intermediate states, which can lead to add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Further simulations have shown that the magnetic properties and magnetization dynamics of such nanostructured systems strongly depend on the lateral dimensions of the system as well as on the wire diameters. 22 This article aims at investigating the influence of the lateral dimensions, tailored by e-beam lithography, of a real fourfold magnetic structures made with lateral dimensions between 160 nm and 400 nm. The shape of the samples presented can be classified between magnetic rings with their vortices and fourfold wire systems with the possibility of a stable intermediate state for a zero-valued externally applied magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Further simulations have shown that the magnetic properties and magnetization dynamics of such nanostructured systems strongly depend on the lateral dimensions of the system as well as on the wire diameters. 22 This article aims at investigating the influence of the lateral dimensions, tailored by e-beam lithography, of a real fourfold magnetic structures made with lateral dimensions between 160 nm and 400 nm. The shape of the samples presented can be classified between magnetic rings with their vortices and fourfold wire systems with the possibility of a stable intermediate state for a zero-valued externally applied magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…To the date metallic nanoframes have shown outstanding optical 17 , magnetic 18 , and electrochemical 16 properties. For instance, the magnetization of 2D square nanoframes was studied by micromagnetic simulations 19 . Different magnetization reversal processes were obtained when the system size conditions were varied.…”
Section: Introductionmentioning
confidence: 99%
“…In this state, further increasing the external magnetic field leads to small rotations of magnetization, but no irreversible switches, and the full orientation along the external magnetic field could be reached without irreversible steps. On the other hand, intentional shape deviations can be used to stabilize a certain desired magnetic state [27].…”
Section: Introductionmentioning
confidence: 99%